Admission Pattern and Outcome in Paediatric Intensive Care Unit of Tertiary Level Teaching Hospital in Eastern Nepal - Chaudhary, Manoj; Rimal, Hem Sagar; Subedi, Ram Bhakta; Kafle, Tara K (Birat Journal of Health Sciences, 2023)
Introduction: Paediatric Intensive Care Unit (PICU) is a relatively new concept with rapidly growing paediatric subspecialty in resource limited-countries. Introduced in Nepal in the 1980s, the first PICU was established in 1986 in Kanti Children’s Hospital, Kathmandu with 4 beds. Later in BPKIHS in Eastern Nepal. Currently only a few dedicated PICU running in Nepal. Our PICU was started in 2021 with 8 beds in the private sector for the management of critically ill children. Objectives: To study the admission pattern and outcome of the children at our paediatric intensive care unit. Methodology: This was a Cross Sectional Descriptive study conducted at PICU of Birat Medical College Teaching hospital in Eastern Nepal. From August 2021 to July 2022, records of all possible admissions in PICU were reviewed. Demographic profile, diagnosis, outcome and duration of stay were analysed. Results: Out of 260 analysed data, there were 156 (60%) males and 104 (40%) females. Age wise distribution was 101 (38.85%), 82 (31.5%), 38 (14.6%) and 39 (15%) for 1 months-1 year, 1-5 year, 5-10 year and 10-15 year respectively. Disease wise distribution was 129 (49%) respiratory, 49 (18.8%) neurological and 26 (10%) gastrointestinal, mostly infective causes like Pneumonia (78, 30%), Bronchiolitis (34, 13.1%), febrile convulsion (29, 11.2%) meningitis/encephalitis (19, 7.3%), Sepsis (12, 4.6%), dengue (6, 2.3%) other infections (19,6.3 %). In outcome, discharged (231,88.85%), DOPR (5,1.92%), LAMA (4,1.54%), Death (16,6.2%) and Referral (4,1.54%). Mortality was high (11, 38.6%) in under five years. Sepsis (4, 33.3%), Meningitis / encephalitis (3, 15.8%) and pneumonia (4, 5.1%) were the common causes. Mean duration of PICU stay was 2.73 days (median=2). Overall mortality rate was 6.2% (16). Sepsis, LOS and need of mechanical Ventilation were significant predictors of mortality. Conclusion: Respiratory illnesses including infections were common causes of admission with low mortality (6.2%). Sepsis, Meningoencephalitis and pneumonia were common causes of death in our PICU. Sepsis, LOS and need of mechanical Ventilation were significant predictors of mortality.